CLEAR - Anatomy and physiology of the anterior eye. Issue 2 (April 2021) - Downie, Laura E.; Bandlitz, Stefan; Bergmanson, Jan P.G.; Craig, Jennifer P.; Dutta, Debarun; Maldonado-Codina, Carole; Ngo, William; Siddireddy, Jaya Sowjanya; Wolffsohn, James S.
Abstract: A key element of contact lens practice involves clinical evaluation of anterior eye health, including the cornea and limbus, conjunctiva and sclera, eyelids and eyelashes, lacrimal system and tear film. This report reviews the fundamental anatomy and physiology of these structures, including the vascular supply, venous drainage, lymphatic drainage, sensory innervation, physiology and function. This is the foundation for considering the potential interactions with, and effects of, contact lens wear on the anterior eye. This information is not consistently published as academic research and this report provides a synthesis from all available sources. With respect to terminology, the report aims to promote the consistent use of nomenclature in the field, and generally adopts anatomical terms recommended by the Federative Committee for Anatomical Terminology. Techniques for the examination of the ocular surface are also discussed.